Application of mixed reality combined with intelligent management in laparoscopic surgery for the endometrial cancer (混合现实技术联合智能化管理在子宫内膜癌腹腔镜手术中的应用) - FANG Yiming (方一名); YANG Ying (杨英); YAO Chong (姚冲); XIAO Yao (肖瑶) (中西医结合护理)
This paper summarized the key points of nursing cooperation for a patient undergoing mixed-reality system guided resection of endometrial malignancy. key points of nursing included preoperative preparation, management of surgical instruments and equipments, preoperative investigation of precision and perioperative nursing cooperation. Based on the establishment of intelligent management system, mixed-reality technology has advantages in postoperative education, postoperative evaluation, preoperative investigation of precision, guidance of intraoperative operation and postoperative clinical teaching. (本文总结1例在混合现实技术引导下行腹腔镜子宫内膜恶性肿瘤切除术的护理配合要点, 包括术前准备、手术物品准备、术中护理配合等。通过构建手术室智能管理平台, 将混合现实技术应用于妇科腹腔镜的术前宣教、术前评估、术前精准讨论、术中操作引导以及术后临床教学, 具有明显优势。)